Sink or swim: Risk stratification of preweaning mortality in harbor seal pups (Phoca vitulina richardii) admitted for rehabilitation. Issue 3 (7th January 2021) - Cole, Justine; Fraser, David
Abstract: To date, few consistent relationships between survival in rehabilitation programs and diagnostic measures recorded upon admission have been identified for harbor seal pups. Veterinary records for 718 unweaned Pacific harbor seal pups ( Phoca vitulina richardii ) admitted to a rehabilitation center were examined to identify clinical factors associated with preweaning survival and develop a triage tool to stratify pups according to their risk of mortality. Physical, serum chemical, and hematological variables were examined and their relationship with survival to weaning was assessed by logistic regression and classification and regression tree (CART) analysis. Survival to weaning was 85.1% and many clinical variables reflecting the pups' age, size, growth, injuries, and blood parameters were associated with the likelihood of survival. A decision tree model, consisting of serum concentrations of phosphorus, sodium, and calcium, successfully stratified harbor seal pups into clinical subgroups according to their preweaning mortality risk. For both the derivation and validation cohorts, pups classified as "high risk" had significantly lower odds of survival, while those classified as "low risk" had significantly greater odds of survival. This simple decision tree could serve as a practical triage tool to help identify and direct care towards pups at higher risk of preweaning mortality.